VOSCO GROUP EMPLOYEE PERFORMANCE ENHANCEMENT THROUGH PROACTIVITY AND GROWTH MINDSET - EVIDENCE FROM A PERCEIVED USEFULNESS MEDIATION MODEL - Della Ayu Putri Pakayli; Widiya Dewi Anjaningrum (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Technological advances have revolutionized the café and restaurant industry, impacting employee efficiency. This study seeks to investigate the influence of proactive personality and growth mindset on employee performance, mediated by perceived usefulness, within Vosco Group, utilizing an employee population of 50 staff. The sample was obtained from a segment of the population utilizing a saturated sampling technique. Data were gathered via an online questionnaire and analysis utilizing Intelligent PLS software version 4.10.8. The results indicate that a proactive personality and growth mindset substantially enhance employee performance, with perceived usefulness acting as a crucial mediator. The perceived usefulness of technology consistently mediates the relationship, but the impact fluctuates based on the degree of individual adaptability to technological advancement. These findings underscore the necessity of providing employees with intuitive technical tools and customized training programs to enhance their flexibility and productivity. This research enhances organizational psychology theory by emphasizing the importance of proactivity and a growth mindset in augmenting employee performance, while also offering practical insights for management in formulating human resource development strategies that leverage technology effectively. Organizations can enhance performance by cultivating a growth mindset culture and recruiting individuals with proactive characteristics. Future research should investigate more variables and extend the study to other industries to improve generalizability.Keywords: Proactive Personality, Growth Mindset, Perceived Usefulness, Employee Performance